2014 International Joint Conference on Neural Networks (IJCNN) 2014
DOI: 10.1109/ijcnn.2014.6889657
|View full text |Cite
|
Sign up to set email alerts
|

Off-line handwritten Thai name recognition for student identification in an automated assessment system

Abstract: In the field of pattern recognition, off-line handwriting recognition is one of the most intensive areas of study. This paper proposes an automatic off-line Thai language student name identification system which was built as a part of a completed off-line automated assessment system. There is limited work undertaken in developing off-line automatic assessment systems using handwriting recognition. To the authors' knowledge, none of the work on the proposed system has been performed on the Thai language. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For HPCHC OFLAS, it was also found that the accuracy rate obtained when applying MDF3 [5] to HPCHC OFLAS was 95.7 1% compared to 94.09% when applying MDF. With CH, the best recognition and accuracy rates were obtained when applying MDF or MDF3 [5] to the CH OFLAS.…”
Section: Oflas Evaluationsmentioning
confidence: 90%
See 1 more Smart Citation
“…For HPCHC OFLAS, it was also found that the accuracy rate obtained when applying MDF3 [5] to HPCHC OFLAS was 95.7 1% compared to 94.09% when applying MDF. With CH, the best recognition and accuracy rates were obtained when applying MDF or MDF3 [5] to the CH OFLAS.…”
Section: Oflas Evaluationsmentioning
confidence: 90%
“…Recognition, Accuracy, and Efficiency Rates best efficiency rate of 80. 12% was obtained when using MDF3 [5] with the OFLAS.…”
Section: Oflas Evaluationsmentioning
confidence: 96%
“…All samples were scanned at 300 dpi and stored in grey-level format, then were binarised and saved in Portable Network Graphics (PNG) format. [4]. Another aspect to mention here is zoning.…”
Section: A Data Collectionmentioning
confidence: 99%
“…The heads of a character can be found in various locations. Thai characters can be divided into three types according to the head [4], which are: 1) No-head character, for example, "ก" for a consonant, "า" for a vowel, and ‫"|"‬ for a voice tone mark.…”
Section: A Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation